The fall of princes [large type] : a novel - Goolrick, Robert, 1948- (Wheeler Publishing, 2015)
"1980s Manhattan shimmers like the mirage it was, as money, power, and invincibility seduce a group of young Wall Street turks. Together they reach the pinnacle, achieving the kind of wealth that grants them access to anything--and anyone--they want. Until, one by one, they fall."--From publisher.